The weld toe improved by a laser remelting process in comparison with a classic TIG-dressing technology - Lago, Ján; Bokůvka, Otakar; Nový, František; Oravcová, Monika (Univerzita Pardubice, 2014)
This paper deals with usage of a laser beam as a new technology for a weld toe improvements.The aim is to show the possibilities of using laser beam for increasing the fatigue life of welds. The conclusions of this work are compared with conclusions from works based on the classic TIG dressing technology. The main difference between the laser and TIG is the way and amount of heat input. This difference caused the difference in the weld toe shape and also the incurred structures after the remelting process. The experimental work was carried out on the Domex 700® steel. The weld joint was manufactured from two identical Domex® 700 plates. For experimental work the double V weld shape has been chosen. The welding was carried out by the MAG welding with CO2 protective atmosphere. The solid state pulse Nd-YAG laser was used for the remelting process. The experimental work is focused on the weld toe shape after the remelting process and identification ofof incurred structures after the remelting process brings the metallographic analyses. The microhardness measurement has shown the structural hardness state after the remelting process.